1 Corinthians - Manetsch, Scott M (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2017)
"In this volume of the Reformation Commentary on Scripture, Scott Manetsch guides readers through a diversity of Reformation-era commentary on 1 Corinthians. Within this volume, readers will encounter familiar voices and discover lesser-known figures from a variety of theological traditions, including Lutherans, Reformed, Radicals, Anglicans, and Roman Catholics. Drawing upon a variety of resources--including commentaries, sermons, treatises, and confessions--many of which appear here for the first time in English, it provides resources for contemporary preachers, enables scholars to better understand the depth and breadth of Reformation commentary, and helps all Christians cling to the things of first importance."--Back cover.
A guide to using this commentary -- General introduction -- Introduction to 1 Corinthians -- Commentary on 1 Corinthians -- Map of Europe at the time of the Reformation -- Timeline of the Reformation -- Biographical sketches of Reformation-era figures and works -- Bibliography.
Includes bibliographical references (pages 492-498) and indexes.
Keywords: Bible. -- Commentaries